Multi‐scale habitat modelling identifies spatial conservation priorities for mainland clouded leopards (Neofelis nebulosa). Issue 10 (18th July 2019) - Macdonald, David W.; Bothwell, Helen M.; Kaszta, Żaneta; Ash, Eric; Bolongon, Gilmoore; Burnham, Dawn; Can, Özgün Emre; Campos‐Arceiz, Ahimsa; Channa, Phan; Clements, Gopalasamy Reuben; Hearn, Andrew J.; Hedges, Laurie; et al.
Abstract: Aim: Deforestation is rapidly altering Southeast Asian landscapes, resulting in some of the highest rates of habitat loss worldwide. Among the many species facing declines in this region, clouded leopards rank notably for their ambassadorial potential and capacity to act as powerful levers for broader forest conservation programmes. Thus, identifying core habitat and conservation opportunities are critical for curbing further Neofelis declines and extending umbrella protection for diverse forest biota similarly threatened by widespread habitat loss. Furthermore, a recent comprehensive habitat assessment of Sunda clouded leopards ( N. diardi ) highlights the lack of such information for the mainland species ( N. nebulosa ) and facilitates a comparative assessment. Location: Southeast Asia. Methods: Species–habitat relationships are scale‐dependent, yet <5% of all recent habitat modelling papers apply robust approaches to optimize multivariate scale relationships. Using one of the largest camera trap datasets ever collected, we developed scale‐optimized species distribution models for two con‐generic carnivores, and quantitatively compared their habitat niches. Results: We identified core habitat, connectivity corridors, and ranked remaining habitat patches for conservation prioritization. Closed‐canopy forest was the strongest predictor, with 25% lower Neofelis detections when forest cover declined from 100 to 65%. A strong, positive association with increasing precipitation suggests ongoing climate change as a growing threat along drier edges of the species' range. While deforestation and land use conversion were deleterious for both species, N. nebulosa was uniquely associated with shrublands and grasslands. We identified 800 km 2 as a minimum patch size for supporting clouded leopard conservation. Main conclusions: We illustrate the utility of multi‐scale modelling for identifying key habitat requirements, optimal scales of use and critical targets for guiding conservation prioritization. Curbing deforestation and development within remaining core habitat and dispersal corridors, particularly in Myanmar, Laos and Malaysia, is critical for supporting evolutionary potential of clouded leopards and conservation of associated forest biodiversity.